High responsivity UV detector based on TiO2-rGO nanocomposite material - Zhumabekov, A.; Kassanova, A.; Ispulov, N.; Dossumbekov, K.; Ospanova, Zh.; Dossanov, T.; Kurmanov, A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The influence of reduced graphene oxide and the optoelectronic characterictics of a nanocomposites based on rGO and TiO2 were studied. Surface morphology and Raman spectra of nanocomposite materials indicate the presence of initial components. It has been illustrated that during hydrothermal synthesis further reduction of rGO occurs, i.e. the variety of oxygen-containing groups decreases. Studies of current-voltage characteristics have displayed the availability of rGO in the nanocomposite leads to an increase in the photo induced current to more than 40 μA. Next, the photoresponsivity of the samples was determined, which is three orders of value higher than pure titanium dioxide for nano-composite material. And the detectivity also increased 9 times. This parameter allows you to identify the performance of the device. In this regard, the UV detector based on nanocomposite has a higher performance. Studies also show a decrease in reaction time to light irradiation. When irradiated, the nanocomposite material reacts to light three orders of magnitude faster than TiO2.
TiO2-rGO нанокомпозиті негізіндегі жоғарысезімтал ультракүлгін детектор
Высокочувствительный УФ детектор на основе нанокомпозита TiO2–rGO
Keywords: graphene oxide; titanium dioxide; Raman spectra; optoelectronic properties; UV detectors